Perbedaan hasil belajar dan motivasi belajar siswa dengan menggunakan model PBL dan pembelajaran konvensional berbantuan media iSpring pada materi laju reaksi - Hengki Wijaya Aritonang; Moondra Zubir (ARKA INSTITUTE, 2022)
This study aims to determine whether there is a significant difference in student learning outcomes and student learning motivation who are taught using the PBL model assisted by the Ispring media with the conventional learning model assisted by the iSpring media on the rate material at PAB 8 Saentis Private High School. The research population was all students of class XI SMA Private PAB 8 Saentis. The sample consisted of class XI students of SMA Swasta PAB 8 Saentis, which consisted of 2 classes, namely the experimental class (XI IPA 2) with the PBL model and the control class (XI IPA 3) with the conventional model. The instruments used are test and non-test instruments. The student learning outcomes data were first tested for normality and homogeneity, where the results obtained by the two samples were normally distributed and homogeneous. Hypothesis testing was carried out using the independent sample t-test, the results of this study showed that in hypothesis 1, a sig value of 0.001 was produced at a significance level of 5% (α= 0.05). if the value of sig < then Ho is rejected. Thus , it shows that there are differences in student learning outcomes who are taught using the PBL model assisted by the Ispring media with the conventional learning model assisted by the iSpring media . while hypothesis 2 obtained a sig value of 0.04 indicating differences in student learning motivation and hypothesis 3 obtained a sig value of 0.035 indicating a correlation between motivation and student learning outcomes who were taught using the PBL model assisted by the Ispring media with the conventional learning model assisted by the iSpring media.